' street water': A community project to discover the underground network that connects the city with its rivers. (1st March 2013) - Vianna, Rachel De Sousa; Aragão, Gaby De
This is the story of 'Street Water Project', which took place in the neighbourhood of Santo Antônio, in Belo Horizonte, Brazil, between November 2010 and July 2011. The activities consisted of art and environment workshops in schools and poetic interventions in public spaces designed to raise awareness of the population regarding the water sources that supply the city.Esta é a história do projeto Água da Rua, realizado no Bairro Santo Antônio, na cidade de Belo Horizonte, Brasil, entre novembro de 2010 e julho de 2011. Tendo como objetivo conscientizar a população sobre os recursos hídricos que abastecem a cidade, o projeto promoveu oficinas de arte e de educação ambiental em escolas e organizou intervenções poéticas em espaços públicos.